Stranded Assets dalam Industri Migas: Perspektif Akuntansi dan Dampaknya terhadap Laporan Keuangan - Zahra, Asywariani; Fakhirah, Siti Bunayyah; Sapitri, Ayu; Tjandrakirana DP, Rina (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the phenomenon of stranded assets in the oil and gas (O&G) industry and examine its impact on financial statements from an accounting perspective. The global transition toward a low-carbon economy has increased the risk of asset value decline in the fossil energy sector, potentially affecting corporate financial stability and long-term investment decisions. This research employs a Systematic Literature Review (SLR) method by analyzing scientific articles indexed in Scopus and SINTA from 2021 to 2026, ensuring a comprehensive and up-to-date synthesis of existing studies. The findings indicate that stranded asset risks are driven by regulatory changes, advancements in renewable energy technologies, and shifts in global economic conditions, which render certain oil and gas assets economically unviable. In addition, increasing environmental awareness and policy pressures further accelerate the obsolescence of carbon-intensive assets. From an accounting perspective, this phenomenon leads to a higher likelihood of asset impairment, changes in asset useful life estimates, and the need for enhanced risk disclosure in financial reporting. It also raises concerns regarding the accuracy of asset valuation and the transparency of financial statements. Furthermore, the study identifies a gap between corporate sustainability commitments and accounting practices that have not fully reflected energy transition risks. Therefore, adjustments in accounting standards and financial reporting practices are necessary to better accommodate stranded asset risks and ensure the relevance, transparency, and reliability of financial information for stakeholders in a rapidly evolving energy landscape.